2017
DOI: 10.1093/nar/gkx328
|View full text |Cite
|
Sign up to set email alerts
|

In mammalian foetal testes, SOX9 regulates expression of its target genes by binding to genomic regions with conserved signatures

Abstract: In mammalian embryonic gonads, SOX9 is required for the determination of Sertoli cells that orchestrate testis morphogenesis. To identify genetic networks directly regulated by SOX9, we combined analysis of SOX9-bound chromatin regions from murine and bovine foetal testes with sequencing of RNA samples from mouse testes lacking Sox9. We found that SOX9 controls a conserved genetic programme that involves most of the sex-determining genes. In foetal testes, SOX9 modulates both transcription and directly or indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
93
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(107 citation statements)
references
References 97 publications
8
93
0
Order By: Relevance
“…4 and 5), confirming the previous report of in utero VCZ exposure to lower SOX9 expression [50]. Exploration of the downstream targets of SOX9 has identified several genes, including Pdgfa [51] and Amh [52,53]. VCZ lowered transcript levels of SC genes, including Pdgfa, Dhh, Amh, and Sox9 as well as Nr5a1 (Fig.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…4 and 5), confirming the previous report of in utero VCZ exposure to lower SOX9 expression [50]. Exploration of the downstream targets of SOX9 has identified several genes, including Pdgfa [51] and Amh [52,53]. VCZ lowered transcript levels of SC genes, including Pdgfa, Dhh, Amh, and Sox9 as well as Nr5a1 (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…It has been demonstrated that SOX9 was able to bind the Pdgfa promoter to increase its expression in the fetal mouse testis [51]. PDGFA, the product of Pdgfa, was reported to be the pivotal factor to guide FLC differentiation because knockout of PDGFA receptor (Pdgfra) resulted in the disrupted FLC development in the fetus with reduced steroidogenesis in mice [37] and null mutation of PDGFA also blocked Leydig cell development in mice during puberty [54].…”
Section: Discussionmentioning
confidence: 99%
“…In eutherian mammals, sex differentiation stems from a critical decision made in the bipotential fetal genital ridges whether to adopt a testicular or ovarian fate. In the presence of a Y chromosome, the expression of the Y-linked transcription factor SRY (sex-determining region Y) in the indifferent genital ridges activates its target gene Sox9 (SRY-box 9), also encoding a transcription factor, which subsequently drives and coordinates the cascade of gene expression leading to the formation of fetal testes (Koopman et al, 1991;Li et al, 2014;Rahmoun et al, 2017;Sekido and Lovell-Badge, 2008;Vidal et al, 2001). In the absence of SRY, RSPO1 (R-spondin 1)/WNT4 (wingless-type MMTV integration site family, member 4)/ CTNNB1 (catenin, beta 1) and FOXL2 (forkhead box L2) induce an alternative set of transcriptional programs, giving rise to fetal ovaries (Chassot et al, 2008;Liu et al, 2009;Ottolenghi et al, 2007;Schmidt et al, 2004;Uda et al, 2004;Vainio et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most important genes required for sex determination ( SRY, SOX9, NR5A1, and FOXL2 ) encode transcription factors [Baetens et al, 2016] that are necessary for the precise spatio-temporal regulation of a range of downstream genes [Rahmoun et al, 2017]. Transcription factors can recruit co-activators to remodel the chromatin and alter histone modifications [Rada-Iglesias, 2014].…”
mentioning
confidence: 99%